Inclusion Complex of Novel Curcumin Analogue CDF and β-Cyclodextrin (1:2) and Its Enhanced In Vivo Anticancer Activity Against Pancreatic Cancer - Dandawate, Prasad R. (2012)
PURPOSE: Several formulations have been proposed to improve the systemic delivery of novel cancer therapeutic compounds, including cyclodextrin derivatives. We aimed to synthesize and characterize of CDF-β-cyclodextrin inclusion complex (1:2) (CDFCD). METHODS: The compound was characterized by Fourier transform infrared, differential scanning calorimetry, powder X-ray diffraction studies, H1 & C13 NMR studies and scanning electron microscopic analysis. Its activity was tested against multiple cancer cell lines, and in vivo bioavailability was checked. RESULTS: CDF-β-cyclodextrin was found to lower IC(50) value by half when tested against multiple cancer cell lines. It preferentially accumulated in the pancreas, where levels of CDF-β-cyclodextrin in mice were 10 times higher than in serum, following intravenous administration of an aqueous CDF-β-cyclodextrin preparation. CONCLUSIONS: Novel curcumin analog CDF preferentially accumulates in the pancreas, leading to its potent anticancer activity against pancreatic cancer cells. Synthesis of such CDF-β-cyclodextrin self-assembly is an effective strategy to enhance its bioavailability and tissue distribution, warranting further evaluation for CDF delivery in clinical settings for treatment of human malignancies.